Soil inoculation with symbiotic microorganisms promotes plant growth and nutrient transporter genes expression in durum wheat - Saia, Sergio; Rappa, Vito; Ruisi, Paolo; Abenavoli, Maria Rosa; Sunseri, Francesco; Giambalvo, Dario; Frenda, Alfonso S.; Martinelli, Federico (Frontiers in Plant Science, 2015)
In a field experiment conducted in a Mediterranean area of inner Sicily, durum wheat was inoculated with plant growth-promoting rhizobacteria (PGPR), with arbuscular mycorrhizal fungi (AMF), or with both to evaluate their effects on nutrient uptake, plant growth, and the expression of key transporter genes involved in nitrogen (N) and phosphorus (P) uptake. These biotic associations were studied under either low N availability (unfertilized plots) and supplying the soil with an easily mineralizable organic fertilizer. Regardless of N fertilization, at the tillering stage, inoculation with AMF alone or in combination with PGPR increased the aboveground biomass yield compared to the uninoculated control. Inoculation with PGPR enhanced the aboveground biomass yield compared to the control, but only when N fertilizer was added. At the heading stage, inoculation with all microorganisms increased the aboveground biomass and N. Inoculation with PGPR and AMF+PGPR resulted in significantly higher aboveground P compared to the control and inoculation with AMF only when organic N was applied. The role of microbe inoculation in N uptake was elucidated by the expression of nitrate transporter genes. NRT1.1, NRT2, and NAR2.2 were significantly upregulated by inoculation with AMF and AMF+PGPR in the absence of organic N. A significant down-regulation of the same genes was observed when organic N was added. The ammonium (NH4+) transporter genes AMT1.2 showed an expression pattern similar to that of the NO3- transporters. Finally, in the absence of organic N, the transcript abundance of P transporters Pht1 and PT2-1 was increased by inoculation with AMF+PGPR, and inoculation with AMF upregulated Pht2 compared to the uninoculated control. These results indicate the soil inoculation with AMF and PGPR (alone or in combination) as a valuable option for farmers to improve yield, nutrient uptake, and the sustainability of the agro-ecosystem.